2021
DOI: 10.1080/21505594.2021.1972201
|View full text |Cite
|
Sign up to set email alerts
|

Roborovski hamster (Phodopus roborovskii) strain SH101 as a systemic infection model of SARS-CoV-2

Abstract: Severe acute respiratory syndrome CoV-2 (SARS-CoV-2) is currently causing a worldwide threat with its unusually high transmission rates and rapid evolution into diverse strains. Unlike typical respiratory viruses, SARS-CoV-2 frequently causes systemic infection by breaking the boundaries of the respiratory systems. The development of animal models recapitulating the clinical manifestations of COVID-19 is of utmost importance not only for the development of vaccines and antivirals but also for understanding the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 60 publications
(65 reference statements)
0
24
0
Order By: Relevance
“…Whilst the work reported within was conducted with Golden Syrian hamsters, other hamster species have also been reported to serve as small animal models in SARS-CoV-2 research, including cardiomyopathy J2N-k [20] and Roborovski strains [21]. The set-up described could thus be transferable for these models too.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the work reported within was conducted with Golden Syrian hamsters, other hamster species have also been reported to serve as small animal models in SARS-CoV-2 research, including cardiomyopathy J2N-k [20] and Roborovski strains [21]. The set-up described could thus be transferable for these models too.…”
Section: Discussionmentioning
confidence: 99%
“…RNA in the CNS as well as inflammation and changes in the neurovascular system [17,30]. Although the Syrian hamster has been used most frequently in hamster studies, it was recently shown that, in Roborovski dwarf hamsters, inbred hamsters, transgenic hamsters expressing human ACE2, and obese hamsters, SARS-CoV-2 infection resulted in more severe disease and systemic spread, including virus spread to the CNS [88][89][90][91].…”
Section: Trends In Neurosciencesmentioning
confidence: 99%
“…Missing is an efficacy model that recapitulates the acute lung injury of life-threatening COVID-19, thereby offering a relevant experimental platform to test the effect of molnupiravir on mitigating lung damage caused by different VOC and explore the impact of treatment on disease outcome. We selected Roborovski dwarf hamsters as a candidate model for this study, since these dwarf hamsters developed acute diffuse alveolar pneumonia and succumbed to infection 22,23 when challenged with original SARS-CoV-2 isolates 4 from 2020.…”
Section: Main Textmentioning
confidence: 99%